Building AI applications with LangChain and GPT - Vankrunkelsven, Vincent (Packt Publishing, 2025)
Embark on a journey to build AI-powered applications using LangChain and GPT-4o Mini in this hands-on, interactive video. Learn how to create a specialized chatbot that utilizes scikit-learn documentation to answer complex questions with precision. This course guides you through every step-from installation to data preparation-while covering essential topics such as embedding documentation with OpenAI's Embed API, estimating embedding costs, and efficiently storing embeddings in a vector database. You'll gain practical experience querying the database, managing document chunks and tokens, and using LangGraph to develop a responsive chat interface. By the end of the course, you will have the skills to build a fully functional AI chatbot that provides accurate, real-time answers, and learn how to optimize processing efficiency and chatbot performance throughout the development process.
"DataLab" : DataLab is a learning solution designed to empower individuals and teams to explore data, build skills, and solve real-world problems. With interactive content, hands-on exercises, and a focus on practical application, DataLab helps learners turn data curiosity into confident capability-no matter where they start. - Online resource; title from title details screen (O'Reilly, viewed April 9, 2025)
Keywords: Application software -- Development; Artificial intelligence; Computer programming; Application program interfaces (Computer software); Logiciels d'application; Développement; Intelligence artificielle; Programmation (Informatique); Interfaces de programmation d'applications; artificial intelligence; computer programming; APIs (interfaces); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet